Navigating extreme weather events: An anthropological investigation - Perin, Ridah (Environmental Humanities, 2026)
The aim of this study was to investigate how do people respond to extreme weather events (EWEs), paying special attention to heavy rainfall. The data and literature gathered unearths strategies and tactics embedded in the social structure of the area of Crawford. These strategies and tactics are either manipulated or reconfigured in patterns of individuality, to gauge what necessary actions are required to mitigate the impacts of heavy rainfall. These approaches were used to answer the foundational question of this study, what roles do existing social relationships play in people's perceptions and responses to extreme weather events? By utilising qualitative research techniques, this study argues that residents of a middle-income neighbourhoods like Crawford respond, adapt and prepare for extreme rainfall in individualised manners. Contrary to areas of less socioeconomic standing who utilise communal strategies such as conviviality to address the challenges heavy rainfall brings.